Increased training intensity and reduced volume for 12 weeks has detrimental effects on swimmers maximal oxygen uptake - Pedersen, M. T.; Kilen, A.; Larsson, T. H.; Jørgensen, M; Rocha, B.; Nordsborg, N. B. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: The training volume of elite swimmers often reaches 40-50 km per week. Recent reports suggest that an increased amount of supra-maximal interval exercise, carried out as 6-12 times 30 s all-out exercise separated by 3 min of rest, can improve the performance of trained non-elite runners, despite a 25-80 % reduction in training volume. The reduction in volume resulted in an improved running economy but no change in maximal aerobic power. METHODS: A group of male (N=20; 19±3 yrs, mean±SD) and female (N=11; 18±3 yrs) elite swimmers were randomly allocated to an intensity training group (IG, N=16) and a control group (CG, N=15). For 12 weeks, CG carried out their normal training of 25-50 km pr week including supra- maximal high intensity bouts 1-2 times per week. IG swimmers reduced their training volume 50% relative to CG and performed at least 4 sets per week of supra-maximal interval training. Before and after the training period, oxygen uptake (VO2) was measured during swimming at two different sub maximal speeds, followed by a test of VO2-max using stepwise increases in swimming speed until exhaustion. In addition swimmers performed a set of 5x200 m starting every 5 min (1-3 being easy sub-maximal swims; the 4th a hard effort and the 5th an all out effort). RESULTS: VO2 was unchanged during submaximal swimming. In IG Figures for VO2 at the highest submaximal velocity before the training period was 2.56 ± 0.78 l/min and after the training period 2.53 ± 0.94 l/min. For CG the same figures were 2.65±0.64 and 2.59±0.54 l/min respectively. For VO2-max there was a significant decrease (P<0.05) in IG from before (3.93±0.81 l/min) to after the training period (3.78±0.94 l/min). There were no changes in VO2- max in CG (Before: 3.85 ±0.71; after 3.84±0.66 l/min). There were no significant changes in 200 m performance. In IG the mean velocity of the 5th 200 m was 1.50±0.08 m/s before the training period and 1.51±0.08 m/s after the training period. For CG the same figures were 1.53±0.09 DISCUSSION: The major findings in this study were that and 1.51±0.08 m/s. reduced training, despite more than a doubling of supra-maximal interval bouts, had a detrimental effect on VO2-max but not on swimming economy or performance in 200 m swimming in this group of elite swimmers. Apparently, a high training volume is required to maintain VO2-max in athletes that depend on their upper body musculature and possibly VO2-max is not a good predictor of 200 m freestyle.